2020
DOI: 10.1038/s41598-020-68681-0
|View full text |Cite|
|
Sign up to set email alerts
|

1.2 MV/cm pulsed electric fields promote transthyretin aggregate degradation

Abstract: Numerous theoretical studies have been conducted on the effects of high-voltage electric fields on proteins, but few have produced experimental evidence. To acquire experimental data for the amyloid disassemble theory, we exposed transthyretin aggregates to 1 ns 1.26 MV/cm pulsed electric fields (PEFs) to promote transthyretin degradation. The process produced no changes in pH, and the resulting temperature increases were < 1 °C. We conclude that the physical effects of PEFs, rather than thermal or chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…One of them could be protein-unfolding provoked by electroporation. Theoretically, the orders of magnitude do not fit: According to a number of simulations, protein unfolding by an electric field requires intensities of 10 6 –10 7 V/cm, much higher than the ∼10 3 V/cm commonly used for electroporation delivery. Quantum mechanics calculations predict that a polyalanine helix would be disrupted from 2.5 × 10 6 V/cm.…”
Section: Methodsmentioning
confidence: 99%
“…One of them could be protein-unfolding provoked by electroporation. Theoretically, the orders of magnitude do not fit: According to a number of simulations, protein unfolding by an electric field requires intensities of 10 6 –10 7 V/cm, much higher than the ∼10 3 V/cm commonly used for electroporation delivery. Quantum mechanics calculations predict that a polyalanine helix would be disrupted from 2.5 × 10 6 V/cm.…”
Section: Methodsmentioning
confidence: 99%
“…The prominent computational molecular dynamics simulation examples comprise protein rotation [21] , change of the secondary structure [22] or dissociation of polymeric protein complexes [23] , unfolding [24] and many more [25] . Experiments have confirmed that protein secondary structure can be affected by an EF [26] and, furthermore, have shown that EF can affect protein enzymatic function [20] , [26] , [27] , self-assembly ability [28] or cause dissociation of protein aggregates [29] .…”
Section: Introductionmentioning
confidence: 85%
“…Previously, we experimentally demonstrated that intense electrical pulses on the order of 20 MV/m destroy urease protein in its aqueous solution using the specially adjusted electrophoresis [1]. Moreover, we reported the 100 MV/m-class electrical pulses disintegrate transthyretin aggregate [2]. Here, we investigated the primary, secondary and tertiary structures in Bovine Serum Albumin (BSA), exposed to 10 PEFs with the field up to 130 MV/m, by characterizing the structures, molecular weight and size.…”
Section: Experimental Study Of Proteins Under Strong Electric Fields ...mentioning
confidence: 99%